Engaging Leadership: How to Promote Work Engagement? - Schaufeli, Wilmar (Frontiers in Psychology, 2021)
This paper introduces the notion of engaging leadership and reviews the empirical work done so far. Engaging leadership is defined as leadership behavior that facilitates, strengthens, connects and inspires employees in order to increase their work engagement. It can be measured with a reliable and valid self-report scale. As predicted by Self-Determination Theory, on which the concept of engaging leadership is based, basic need satisfaction mediates the relationship between engaging leadership and work engagement. This is true both for individual employees as well as the team level. In addition, job characteristics (job demands and job resources) seem to play a similar mediating role, just as personal resources. Furthermore, research shows that engaging leadership has a beneficial effect on individual and team performance which illustrates its relevance for organizations. Future research should focus, amongst others, on the opposite of engaging leadership (i.e., disengaging leadership) and interventions to foster engaging leadership. Moreover, alternative affective, cognitive and behavioral pathways should be explored that might play a role in addition to the motivational (through need fulfillment) and material (through job characteristics) pathways that have been investigated so far.